Normative Observational Nerve Ultrasound Values in School-Age Children and Adolescents and Their Application to Hereditary Neuropathies - Grimm, Anna-Sophie; Schubert, Charlotte; Grimm, Alexander; Stahl, Jan-Hendrik; Küpper, Hanna; Horber, Veronka; Kegele, Josua; Willikens, Sophia; Wittlinger, Julia; Serna-Higuita, Lina; Winter, Natalie; Groeschel, Samuel (Frontiers in Neurology, 2020)
Abstract Backgrounds: To establish nerve ultrasound reference data in 8 to 17 years-old children and adolescents and to compare those data to younger children, adults and age-matched children with polyneuropathies. Methods: High-resolution ultrasound of the nerves was performed in 117 healthy children and adolescents at 20 predefined landmarks in the neck and the extremities of both sides. Mean values, side-to side differences and intraneural ratios as well as upper limits have been calculated. In a second step comparison to 25 children and adolescents of the same age range with proven hereditary and acquired neuropathies and lysosomal storage diseases has been done. Results: Nerve growth correlates significantly with age and reaches adult values at the age of around 15 years. The influence of body mass index and gender is negligible at most segments. By the use of age-specific upper limits, nerve enlargement could be seen in distinct types of neuropathies, particularly in demyelinating hereditary and inflammatory types – comparable to findings in adults -, but also in rare lysosomal storage diseases. Conclusion: Nerve size correlates with age during childhood and reaches climax in younger adults. Age-matched reference data are inevitable to differ hypertrophic from non-hypertrophic nerve damage, e.g. in neuropathies.